Arctic Biodiversity Freshwater Monitoring Plan Annual Report 2014: Annual report on the implementation of the CBMP's Arctic Freshwater Biodiversity Monitoring Plan - Lento, J.; J. Culp, W; Christoffersen, K.; Guðbergsson, G.; Liljaniemi, P.; Sandøy, S.; Whitman, M.; Zimmerman, C. (Conservation of Arctic Flora and Fauna (CAFF), 2014)
This report describes the progress made since December 2012, when implementation of the CBMP-Freshwater Plan began.